TEACHING ENGLISH TO YOUNG LEARNERS: A Case Study of Three Elementary School Teachers in Solok, West Sumatera - Murni, Ratna (2009)
This study investigates teachers' way in planning and in implementing their English teaching to young learners and the way they assess their students' learning progress and achievement. More specifically, this is a case study of three elementary school English teachers. Participants of this research are three English teachers at three Elementary Schools in Solok, West Sumatera. The data of this study are collected through questionnaire, interview, observation and documents analysis. In other words, validity of data is obtained through triangulation. The data are analyzed qualitatively through the following stages: transcribing the raw data, coding the data, categorizing the data, synthesizing the data, interpreting the data, and making conclusion. Major findings of this study among other are 1) eventhough the teachers conduct the same steps in planning the instruction, the plan is implemented and resulted in different ways; 2) all the teachers taught English integratively, but not all of them teach English contextually; 3) most of the teaching strategies the teacher apply seem effective to meet their teaching objectives; 4) majority of teaching strategies the teachers use are congruent with assessment strategies they apply; 5) regarding teachers' way in assessing students' learning progress and achievement, the teachers use both formative and summative assessment, but with different tendency. There are two implications of this study: practical implication and methodological implication. In terms of practical implication, there are several suggestions proposed. First, it is recommended that quality (teachers' qualification) and quantity (exposure to English) in English teaching should be maximized in order to enhance students' learning. Second, beside having English educational background, elementary school English teachers have to posses sound knowledge of the principles of teaching English to young learners and apply them in their teachings. Third, the teachers should always conduct continious reflection on their teachings and continiously develop their professionalism. In terms of methodological implication, deals with limitations and shortcomings that occur in this study: limited time devoted and participants observed, further studies is recommended to be conducted with longer time and more participants in order to give contribution in another context. The prospect the researcher can consider not only observing the strategies but also facilities, materials, and so on. This study is also expected to give meaningful contribution to the researcher herself, to those in charge for administering English teaching in elementary schools as well as to the English teachers as a whole.